MODIFIKASI KRIPTOGRAFI KLASIK VIGENERE CIPHER MENGGUNAKAN ONE TIME PAD DENGAN ENKRIPSI BERLANJUT - M Ziaurrahman; Ema Utami; Ferry Wahyu Wibowo (Universitas Janabadra, 2019)
The development of communication is increasingly rapid which does not escape from various threats such as eavesdropping or data theft, because that security aspect of data security is now very calculated. Various ways have been done to secure data that contains confidential information. One method used is to scramble the data into unclear content, so that when tapped it will be difficult to find out the actual information content. Encryption techniques by changing and randomizing the original form of data are called cryptography. Vigenere cipher is one type of classical cryptography algorithm that is popular and often used. This Vigenere cipher uses a substitution technique in encrypting the message where each plaintext character in the message will be encrypted into another character in the ciphertext based on the key used. One Pad algorithm is one algorithm that has perfection when encrypting and decrypting it. The basic concept of the One Time Pad algorithm is almost the same as the Vigenere algorithm, except that in this algorithm the key is generated randomly. In this paper, we will explain how to strengthen Vigenere cipher by modifying Vigenere ciphers. Modifications are carried out by applying One Time Pad encryption generated from the key and the next key generation technique using Vigenere encryption continues so that the key used for the coding will be different from the key used previously. With the use of this method, the connection between plaintext and ciphertext will become less and more difficult to solve cryptanalis.Keywords: Cryptography, Modification, Vigenere Cipher, One Time Pad, and Cyber Security.